Determinants of Hybrid Investor Behavior: Selecting Stock in The Islamic Capital Market with Maqasid of Sharia as Moderation - Jalari, Jalari; Anwar , Syamsul; Ardiansyah , Misnen (Millah: Journal of Religious Studies, 2023)
The focal point of this research is the hybrid investor behavior and maqaṣid of sharia. Understanding maqaṣid of sharia is the right solution to negative public perceptions of investment in the Islamic capital market. Hybrid investor behavior comprises two variables: perceived risk and behavioral hybrid, which lead to different results. This study aims to find new theories about the behavior of hybrid investors towards stock options with maqaṣid of sharia as a moderating variable to strengthen scientific thinking to conceptually and contextually identify, evaluate, and execute the existing problems in choosing sharia stocks. This was an explanatory research study with a nonexperimental research design. This study used a quantitative method, and data were collected through questionnaires distributed to hybrid investors in Surakarta areas: Surakarta, Boyolali, Klaten, Sukoharjo, Wonogiri, Karanganyar, and Sragen. It involved 130 investors as research participants. The data were analyzed using Structural Equation Modeling to obtain a model that explains the relationship between the variables on Sharia stock options. This research revealed that the perception of risk has a negative and significant effect on the choice of Islamic stocks. Hybrid behavior has a positive and significant effect on the choice of Islamic stocks. Maqaṣid sharia moderates the effect of risk perception on sharia stock options and does not moderate the effect of hybrid behavior on the choice of sharia stocks.